2017
DOI: 10.1111/maq.12321
|View full text |Cite
|
Sign up to set email alerts
|

From Reproductive Rights to Responsibilization: Fashioning Liberal Subjects in Mexico City's New Public Sector Abortion Program

Abstract: Building on medical anthropology literature that analyzes doctor-patient interactions as a charged site for the production of political subjectivities, I demonstrate how a central feature of Mexico City's new public sector abortion program involves "responsibilization." In accordance with entrenched Ministry of Health objectives, providers transmit a suite of values about personal responsibility and self-regulation through the use of birth control, hinging abortion rights to responsible reproductive subjectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Laws and their enactment ‘are significant because they … reflect dominant social concerns and values’ (Melhuus : 3). Singer's () research on newly legalised abortion in Mexico City, for instance, demonstrates that this outward expansion of reproductive rights essentially reiterated long‐standing state and social values around reproductive responsibility. Undergoing a state‐funded abortion through Mexico City's public abortion program is accompanied by a lesson in responsible sexual practices intended to prevent (another) unwanted pregnancy.…”
Section: Local Moralities Of Assisted Conceptionmentioning
confidence: 99%
“…Laws and their enactment ‘are significant because they … reflect dominant social concerns and values’ (Melhuus : 3). Singer's () research on newly legalised abortion in Mexico City, for instance, demonstrates that this outward expansion of reproductive rights essentially reiterated long‐standing state and social values around reproductive responsibility. Undergoing a state‐funded abortion through Mexico City's public abortion program is accompanied by a lesson in responsible sexual practices intended to prevent (another) unwanted pregnancy.…”
Section: Local Moralities Of Assisted Conceptionmentioning
confidence: 99%
“…Medical anthropologists have shown that in some cases, women who are not able to fit into ideal reproductive behavioral models often ignore their own difficult experiences in favor of support for the idealized reproductive behaviors. These women often understand that they've experienced difficult circumstances but have internalized the narrative that shames them for not partaking in ideal reproductive behaviors (Singer 2017;Gammeltoft 2007). My research shows something slightly different.…”
Section: Amelia: Fractured Carementioning
confidence: 82%
“…But if my research shows anything, it is that this discourse is not necessarily a source of shame for women who do not fit specific models of reproductive behavior, like other anthropologists have found (Singer 2017;Gammeltoft 2007). For the women in my research, the local, wellfunded, healthcare system provided them with the resources they needed to have a positive pregnancy and birth.…”
Section: Global Flows National Ideologies and Maternity Care Within mentioning
confidence: 85%
See 2 more Smart Citations